Komunikasi Lingkungan: Motivasi dan Taktik Komunitas dalam Perbaikan Sosiokultural Masyarakat Pesisir Sungai Banjarmasin - Bambang Dwi Waluyo; Achmad Bayu Chandra Buwono (UIN Antasari Banjarmasin, 2023)
The phenomenon of flooding and damage to river ecosystems in the City of Banjarmasin is one of the unresolved sociocultural problems. The Friends of the River Community is present in the Banjarmasin City community in trying to solve this problem. This paper describes the motivations and tactics of Sahabat Sungai Community in conveying messages of change to riverside communities in Banjarmasin by using methods, strategic ideas, and communication strategies to manage and protect the environment, in an effort to spread messages about environmental sustainability. Sungai about their motivations and tactics and see the direct influence on the riverside community in Banjarmasin. This article contributes to an understanding of agenda setting, environmental communication, and the communication techniques that communities use to convey their messages